Geographical knowledge search, internal R&D intensity and product innovation of clustering firms in Zhejiang, China2. (21st January 2014) - Wu, Aiqi; Wang, Cassandra C.; Li, Shengxiao
Abstract While a great deal of literature has paid attention to knowledge spillover on innovation, this study argues that geographical knowledge search that lays much emphasis on firm strategies merits more attention. This paper examines the effect of geographical knowledge search strategies, such as local/non‐local search depth and local/non‐local search breadth on product innovation. We reveal that while local search depth and breadth as well as non‐local search breadth exert a significant influence, non‐local search depth produces a negative impact on product innovation. Our research suggests that clustering firms' geographical knowledge search strategies and R&D intensity should be highlighted to understand their product innovation.